An Activatable and Reversible Virus‐Mimicking NIR‐II Nanoprobe for Monitoring the Progression of Viral Encephalitis. (25th August 2022) - Chen, Hua‐Jie; Qin, Ying; Wang, Zhi‐Gang; Wang, Lei; Pang, Dai‐Wen; Zhao, Dongbing; Liu, Shu‐Lin
Abstract: Viral encephalitis is an inflammatory disease of the brain parenchyma and caused by various viral infections. In vivo monitoring of the progression of viral infections can aid accurate diagnosis of viral encephalitis and effective intervention. We developed an activatable and reversible virus‐mimicking near‐infrared II nanoprobe consisting of an Fe 2+ ‐coordinated, viral protein‐decorated vesicle encapsulating PbS quantum dots with a 1300 nm fluorescence emission. The probe can cross the blood–brain barrier and monitor real‐time changes in reactive oxygen and nitrogen species concentrations during viral infection by tuning the quenching level of quantum dots and regulating the fusion–fission behavior of vesicles via changes in Fe oxidation state. This switching strategy reduces background noise and improves detection sensitivity, making this nanoprobe a promising imaging agent for dynamic visualization of viral encephalitis and future clinical applications. Abstract : We present an activatable virus‐mimicking NIR‐II nanoprobe based on PbS quantum dots (QDs) encapsulated in a Fe 2+ ‐coordinating viral protein‐decorated vesicle. The probe can cross the blood–brain barrier and monitor real‐time changes in reactive oxygen and nitrogen species concentrations during viral infection, providing a favorable approach for dynamic visualization of viral encephalitis.